2023
DOI: 10.1080/2162402x.2023.2192098
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-associated repair-like Schwann cells suppress anti-tumor T-cells via 12/15-LOX/COX2-associated eicosanoid production

Abstract: Peripheral glia, specifically the Schwann cells (SCs), have been implicated in the formation of the tumor microenvironment (TME) and in cancer progression. However, in vivo and ex vivo analyses of how cancers reprogram SC functions in different organs of tumor-bearing mice are lacking. We generated Plp1-CreERT/tdTomato mice which harbor fluorescently labeled myelinated and non-myelin forming SCs. We show that this model enables the isolation of the SCs with high pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Growth factors and cell cycle inhibitors, such as LOX and CDKN2B, were also present in the blue module and conserved in cross-species analysis. LOX is a tumor suppressor gene, which when mutated in Schwann cells, can suppress T-cells in the melanoma tumor microenvironment [45]. CDKN2B is a cell cycle inhibitor that can induce proliferation when deleted or mutated in a multitude of cancer types [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors and cell cycle inhibitors, such as LOX and CDKN2B, were also present in the blue module and conserved in cross-species analysis. LOX is a tumor suppressor gene, which when mutated in Schwann cells, can suppress T-cells in the melanoma tumor microenvironment [45]. CDKN2B is a cell cycle inhibitor that can induce proliferation when deleted or mutated in a multitude of cancer types [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…In bladder cancer, p53 activates ALOX15B by inhibiting SLC7A11, leading to the induction of ferroptosis in bladder cancer cells [203]. In melanoma tumors, the blocking of ALOX5 or ALOX12-associated eicosanoid production reverses Schwann cell-dependent suppression of anti-tumor T cell activation [251] Current clinical trials targeting malignant glioma have shown promising therapeutic benefits from using herpes simplex virus thymidine kinase (HSV-TK) gene therapy [252]. However, when HSV-TK was combined with ALOX15 using adenoviral vectors in BT4C malignant glioma cells, there was no notable increase in tumor growth inhibition.…”
Section: Perspectives Of Alox15 Transgene a Oncotherapeutic Boostermentioning
confidence: 99%